Management of a Novel Autoimmune Disease, COPA Syndrome, in Pregnancy - Archana Ayyar; Rachel D. Seaman; Kalpalatha Guntupalli; Mary C. Tolcher (Hindawi Limited, 2022)
Background. COPA syndrome is a rare autoimmune disease, demonstrating an autosomal dominant inheritance pattern with variable penetration that occurs more frequently in females than males. This disease manifests in childhood as pulmonary hemorrhage, arthritis, and renal disease. Case. We present a case of obstetric management of a 20-year-old nulligravida patient with a diagnosis of COPA syndrome. Her case was further complicated by multiple antepartum admissions for hypoxemia and a complex psychosocial history of substance use. On her first antepartum admission, rheumatology recommended management with hydroxychloroquine, inhaled corticosteroids (budesonide), and bronchodilators (albuterol inhaler) as needed. On admission for induction of labor, she was again noted to have oxygen desaturations. A chronic thrombus was noted on computed tomography (CT), and a multidisciplinary team was recommended against Valsalva. Thus, she had a primary cesarean delivery. Her postpartum course was only remarkable for improved oxygenation status. Conclusion. Management of COPA syndrome should be performed by a multidisciplinary team including maternal-fetal medicine, rheumatology, and pulmonology specialists. Traditionally, COPA syndrome is treated with immunomodulator therapy often used to treat autoimmune syndromes. However, many of these medications are not well studied or contraindicated in pregnancy. Preconception counseling is recommended both to ensure pregnancy safe medications being prescribed and to provide information on the genetic inheritance of this disease. At time of entry to care, patients should have a baseline work-up including a radiographic imaging, complete blood count, complete metabolic panel, lactate dehydrogenase, and a 24-hour urine protein collection for baseline. Although thought to be rare, COPA syndrome has an autosomal dominance pattern of inheritance with variable penetrance that is more common in females. Thus, incidence of COPA syndrome in pregnancy will likely increase in the future. Further case studies are warranted to optimize management of patients with COPA syndrome in pregnancy.